Bioactive hydrolysates from bovine blood globulins: Generation, characterisation, and in silico prediction of toxicity and allergenicity. (June 2016) - Lafarga, Tomas; Wilm, Matthias; Wynne, Kieran; Hayes, Maria
Highlights: Bovine allergenic peptides identified from globulin proteins derived from beef blood. Sequence analysis of bioactive peptides derived from beef globulin proteins. Identification of ACE-I, renin and DPP-IV inhibitory peptides from beef globulin proteins. Assessment of the toxicity of beef globulin protein derived peptides. Abstract: Two protein fractions rich in γ-globulins (FI) and α- and β-globulins (FII) were generated from bovine blood and hydrolysed with the enzyme papain. The generated hydrolysates showed in vitro angiotensin-I-converting enzyme (ACE-I), renin, and dipeptidyl peptidase-IV (DPP-IV) inhibitory activities. A total of 626 and 2246 peptides were identified by LC-MS/MS from the 1 kDa fractions of FI and FII, and the potential toxicity and allergenicity of these peptides were assessed in silico using three independent predictive approaches. All of the peptides identified from the bioactive blood protein fractions FI and FII were predicted to be non-toxic. However, 72 peptides from FI and 492 peptides from FII were identified as potential allergens with at least two predictive approaches. Results suggested that papain hydrolysates of FI and FII contain potential allergenic peptides, and those products containing such hydrolysates should be labelled correctly in line with Food and Consumer legislation – Regulation (EU) No.1169/2011.